“A terra é um sonho, a luta é uma raiz”: trajetórias de vida e protagonismos de mulheres sem-terra em Tacuru-MS (2000-2023) - Langaro, Sonia Vanessa (2024)
This research is dedicated to studying the life trajectories of landless women in the municipality of Tacuru–MS, located in the border region between Brazil and Paraguay. The primary objective of this study is to understand the leadership of these women in the struggle for land rights, with a focus on those connected to the Carimbó camp. The investigation explores their migrations, life experiences, and work, based on the interpretation of their memories and oral narratives. These women have faced numerous challenges throughout their lives, from the arduous agricultural labor in their childhood to land expropriation, enduring periods of hunger and deprivation, as well as a lack of decent housing. Some even migrated to Paraguay in search of land to live and work on. The research focuses on the narratives of the women who joined the Carimbó camp, established in 2007 and still active as of 2023, despite the adverse political contexts that have disbanded many camped families. The families remaining in the camp live in precarious conditions, nurturing the hope of securing a plot in a settlement. Some have chosen to settle in the urban area of Tacuru but continue to cultivate food to ensure healthy and accessible nourishment, while still holding onto the expectation of owning their land. The research was conducted using the Oral History methodology, alongside the analysis of newspapers, photographs, and documents, with an emphasis on the gender issues that permeate these women's struggle. Moreover, the desire to leave a legacy for future generations emerges as a central element driving these women, even in the face of the adversities they have encountered throughout their lives.